Hubungan Pemberian Alat Permainan Edukatif Dengan Perkembangan Motorik Kasar Pada Balita Usia 1-5 Tahun - Efi Kristiana (2018)
ABSTRACT Award Educational Toys not only make hearts happy. But it is also very have meaning in the development of children, because children have a great chance of acceptance to external stimuli in children. The purpose of this study was to determine the relationship Award Educational Toys with gross motor development in infants aged 1-5 years in the village of Babadan Patianrowo Nganjuk District of the Year 2017. This research is an analytic study with this type of correlation studies. The population is all mothers and children aged 1-5 years in the village of Babadan, District Patianrowo, Nganjuk District, using the technique of random sampling sampling system in order to obtain a sample of 68 respondents. This research was conducted in the month of February 2017. The data was collected using a questionnaire and observation sheet. The independent variables are administration Educational Toys, while the dependent variable is gross motor development in young children 1-5 years old. Data were analyzed using Spearman Rank (Rho) statistical test with α = 0.05.The results showed that 47 respondents (69%) the provision Educational Toys. Meanwhile, gross motor development in infants aged 1-5 years 43 respondents (63%) in the corresponding category. The test results Spearman Rank correlation (Rho) with r = 0.818. Based on the level of interpretation of the correlation coefficient indicates that there is a relationship between the provision Educational Toys with gross motor development in infants aged 1-5 years in the village of Babadan Patianrowo Nganjuk District of the Year 2017 at very strong levels. Based on the results of the above research, the researchers concluded that the Giving Educational Toys Equipment greatly affect the development of gross motor in toddlers. Thus, it is suggested that the mother to give Educational Toys and more to monitor the rough motor development of children according to the age stage.